A Standard European Tank? Technology Transfer and the Quest since 1945 for a Joint International Main Battle Tank within Europe and NATO - Cubbin, Mike (Cranfield University, 2017)
3MT presented at the 2017 Defence and Security Doctoral Symposium.International cooperation in defence has long been a feature of diplomacy, and there are many theoretical advantages to both international technology transfer and standardisation within military alliances, from military organisation and logistics to political consolidation, and on to economic savings in both development and production. International collaboration in the defence industry has produced many successful weapon systems, from technologically advanced fighter aircraft to anti-tank missiles. Given the success of many joint defence projects such as the Tornado and Eurofighter aircraft, and the Roland and Brimstone missile systems, the question emerges as to why there have been no successful collaborative international main battle tank projects. The quest for a standard tank design within NATO began with the Franco-German ‘standard European tank’ project in 1956, and NATO countries have since made several further attempts towards a joint Main Battle Tank (MBT) design. At the time of writing there is talk of yet another potential joint European tank project, this time between France, Germany and possibly Poland. An important question that arises from the many works on armoured warfare, armoured vehicle technology and military technology transfer then is, why has NATO yet to agree and produce a standard tank despite several attempts since 1945? To date, there has been only one successful truly collaborative main battle tank design, and that was the Anglo-American Mark VIII ‘International’ in 1917.
Keywords: 'Tanks'; 'NATO'; 'Collaboration'; 'DSDS17 3MT'; 'DSDS17'; 'Engineering Design not elsewhere classified'; 'Defence Studies'